2023
DOI: 10.3389/fmicb.2023.1104944
|View full text |Cite
|
Sign up to set email alerts
|

Different and unified responses of soil bacterial and fungal community composition and predicted functional potential to 3 years’ drought stress in a semiarid alpine grassland

Abstract: IntroductionSoil microbial communities are key to functional processes in terrestrial ecosystems, and they serve as an important indicator of grasslands status. However, the responses of soil microbial communities and functional potential to drought stress in semiarid alpine grasslands remain unclear.MethodsHere, a field experiment was conducted under ambient precipitation as a control, −20% and −40% of precipitation to explore the responses of soil microbial diversity, community composition, and predicted fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Third, the worsening of drought stress may lead to soil cracking, land degradation, and changes in the physical environment of the soil (air, water, aggregate structure, etc.) (Fitzpatrick et al, 2017;Wan et al, 2023), making it unsuitable for the propagation and growth of microorganisms. Additionally, studies have indicated that soil microorganisms reduce the loss of nutrients and metabolism under long-term drought stress (Manzoni et al, 2014;Brown et al, 2021), thereby reducing microbial biomass and enzyme production capacity.…”
Section: Effect Of Drought Intensity and Duration On Soil Microbial B...mentioning
confidence: 99%
“…Third, the worsening of drought stress may lead to soil cracking, land degradation, and changes in the physical environment of the soil (air, water, aggregate structure, etc.) (Fitzpatrick et al, 2017;Wan et al, 2023), making it unsuitable for the propagation and growth of microorganisms. Additionally, studies have indicated that soil microorganisms reduce the loss of nutrients and metabolism under long-term drought stress (Manzoni et al, 2014;Brown et al, 2021), thereby reducing microbial biomass and enzyme production capacity.…”
Section: Effect Of Drought Intensity and Duration On Soil Microbial B...mentioning
confidence: 99%
“…Drought significantly alters the composition and structure of fungal communities [25]. Drought affects fungal communities by altering the effective use of soil water.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study showed that the FNC varies with correspondingly different droughts. This finding suggests that under moderate drought (D30%), some less drought‐tolerant fungi died, resulting in an increase in FNC; under severe drought (D50%), fungi with greater drought tolerance or even xerophilic fungi increased their dominance in the fungal community, and their lower mortality led to a significant reduction in FNC (Oliveira et al., 2020; Wan et al., 2023). Fungal necromass increased slightly at D30% treatment and decreased significantly at D50% treatment (Figure 2).…”
Section: Discussionmentioning
confidence: 99%